Space filling elements, Design, BIBE Chair Space Filling Elements as a Form of Tropical Style Dayak Culture Implementation - INAYA ALIFIA FABIANI, INAYA; Rahman, R Ayu Firdausi Novita (Bina Nusantara University, 2024)
In the interior of a room there are filling elements such as floors, walls, and ceilings or forms of space-filling such as furniture and aesthetic elements in it. A design or shape of a room filler describes the concept of what is in a building, if the impression of a room is appropriate it can certainly be accepted from a human point of view, then this can influence the function and emotion in creating a room atmosphere. This design methodology starts from a data collection method containing literature data and typology data, followed by an analysis method in the form of design to the final design. Based on the method described, the design of interior space-filling elements refers to the cultural diversity of the Dayak tribe which is implemented with a modern concept with a tropical theme. The Dayak tribe is of course very closely related to nature based on its geological location, therefore in this design, a lot of wood is used in the material elements to make it suitable. Meanwhile, to add tropical elements, of course, it is necessary to add tropical motifs or patterns to it. The purpose of writing this design is to identify the factors that form the elements of a room that implement Dayak culture in a tropical style. The benefit of this research is to find out what factors influence the design elements of Dayak culture. This design produces structured space-filling elements or refers to concepts analyzed based on literature data and typology.